2018
DOI: 10.2903/sp.efsa.2018.en-1406
|View full text |Cite
|
Sign up to set email alerts
|

In vivo toxicity and genotoxicity of beauvericin and enniatins. Combined approach to study in vivo toxicity and genotoxicity of mycotoxins beauvericin (BEA) and enniatin B (ENNB)

Abstract: Beauvericin (BEA) and Enniatins (ENN) are mycotoxins produced by Fusarium fungi detected in food and feed; there are insufficient data to establish their reference values. To evaluate BEA and ENN oral toxicity, an integrated approach was applied. Among ENN, Enniatin B (ENNB) was selected as test substance. The approach is composed by: i) in vitro and acute in vivo genotoxicity tests; ii) a repeated‐dose oral toxicity study focused on genotoxic, immune, endocrine, nervous endpoints and the reproductive/developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…However, the concentrations were in line with other studies (Viegas et al 2018). Toxicity and toxicokinetics in other species have recently been reviewed by Fraeyman (Fraeyman et al 2017) and as an EFSA supporting document (Maranghi et al 2018), which hopefully makes it possible to risk assess enniatins in the near future.…”
Section: Discussionsupporting
confidence: 81%
“…However, the concentrations were in line with other studies (Viegas et al 2018). Toxicity and toxicokinetics in other species have recently been reviewed by Fraeyman (Fraeyman et al 2017) and as an EFSA supporting document (Maranghi et al 2018), which hopefully makes it possible to risk assess enniatins in the near future.…”
Section: Discussionsupporting
confidence: 81%
“…According to the EFSA CONTAM panel, acute exposure to ENNB does not indicate concern for human health, but that may not be the case in the case of chronic exposure. Based on the repeated-dose ENNB study, the lowest NOAEL has been observed for female mice at 0.18 mg kg −1 bw day −1 for effects on thymus, uterus, and spleen [48]. We converted the NOAEL by applying an interspecies safety factor of 10 to obtain an aRfD of 18 µg kg −1 bw day −1 for humans.…”
Section: Toxicological Reference Dosesmentioning
confidence: 99%
“…Enns and BEA have shown cytotoxic, genotoxic and immunomodulating effects, as well as toxic effects on reproductive systems [39,40]. These toxins have been reported to accumulate in animal tissues and eggs [41].…”
Section: Enniatins (Enns) and Beamentioning
confidence: 99%